2006
DOI: 10.1159/000090340
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Alters Vascular Reactivity by Enhancing COX-Related Vasodilatation in Fetal Ovine Carotids

Abstract: Based on preliminary studies that contractile efficacy was altered in vertebral and basilar arteries from neonatal donors treated with postnatal glucocorticoids, we examined the hypothesis that postnatal dexamethasone (DEX), a glucocorticoid used for respiratory disease in neonates, can alter vascular reactivity. Using near-term fetal lamb carotids, we measured 5-hydroxytryptamine (5-HT) dose-response relationship in DEX-treated and untreated arteries. We found that DEX incubation for 1 h had no effect on 5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…al. has demonstrated that attenuation of 5-hydroxytryptamine-induced constrictions in fetal carotid arteries incubated with dexamethasone can be reversed with Indo, suggesting that there is increased contribution of COX products in the modulation of carotid artery reactivity after exposure to dexamethasone (23). …”
Section: Discussionmentioning
confidence: 99%
“…al. has demonstrated that attenuation of 5-hydroxytryptamine-induced constrictions in fetal carotid arteries incubated with dexamethasone can be reversed with Indo, suggesting that there is increased contribution of COX products in the modulation of carotid artery reactivity after exposure to dexamethasone (23). …”
Section: Discussionmentioning
confidence: 99%
“…For serotonin, ERK activation appeared as a significant downstream component of 5HT receptor activation, particularly in fetal arteries [85]. Incubation with dexamethasone also exhibited a time-dependent ability to attenuate 5HT-induced contractions through a cyclooxygenase-dependent pathway in fetal arteries [86]. Conversely, incubation with dopamine enhanced contractile responses to 5HT [87], suggesting that vasoactive compounds commonly administered to neonates in the NICU may have conflicting effects on cerebrovascular contractility.…”
Section: The 2000s: Calcium Cgmp Pkc and Fetal Cbfmentioning
confidence: 99%